2022
DOI: 10.3390/antiox11112095
|View full text |Cite
|
Sign up to set email alerts
|

Novel Active Food Packaging Films Based on Gelatin-Sodium Alginate Containing Beetroot Peel Extract

Abstract: Currently, the exploration of natural colorants from vegetal waste has gained particular attention. Furthermore, incorporation of these natural sources into biopolymers is an encouraging environmentally friendly approach to establishing active films with biological activities for food packaging. The present study developed bioactive antioxidant films based on gelatin-sodium alginate (NaAlg) incorporated with aqueous beetroot peel extract (BPE). Firstly, the effects of combining gelatin-NaAlg and BPE at 0.25, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 105 publications
(151 reference statements)
1
12
1
Order By: Relevance
“…Chaari et al . (2022) also reported decreased luminance of gelatin‐sodium alginate film with the addition of betacyanin pigment from beetroot peel extract.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Chaari et al . (2022) also reported decreased luminance of gelatin‐sodium alginate film with the addition of betacyanin pigment from beetroot peel extract.…”
Section: Resultsmentioning
confidence: 93%
“…Betalain comprises betacyanin pigment, a red-violet colourant, and betaxanthin pigment, a yellow-orange colourant (Khoo et al, 2022). Chaari et al (2022) also reported decreased luminance of gelatin-sodium alginate film with the addition of betacyanin pigment from beetroot peel extract.…”
Section: Colourmentioning
confidence: 91%
“…In this context, biodegradable polymers, such as edible films, are a promising alternative to synthetic polymers (Paidari et al, 2021;Umaraw et al, 2020). Several studies have been conducted on the antimicrobial and antioxidant effects of active food packaging systems containing plant preservatives on different foods (Bagher Abiri et al, 2023;Chaari et al, 2022;Moosavi-Nasab et al, 2023;Noorbakhesh & Danaee, 2021;Smaoui et al, 2022;Yadav et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Gelatin can be used to obtain edible films [ 26 , 27 , 28 , 29 ] for meat products [ 30 , 31 ] or post-harvest fruit and vegetable [ 32 , 33 , 34 , 35 ] preservation. Mechanical properties such as fragility, rigidity, and brittleness are common in gelatin films, which often require the addition of other compounds to improve their performance such as chitosan [ 36 , 37 , 38 , 39 ], sodium alginate [ 40 ], grapefruit-seed extract and TiO 2 [ 41 ], starch [ 42 ], and plant extracts [ 43 , 44 ]. Whey is a water-soluble compound, with the highest proportion in the composition of milk, in which valuable proteins are dissolved, conferring it with an appreciable nutritional value.…”
Section: Introductionmentioning
confidence: 99%